In-Space Manufacturing: Technologies, Challenges, and Future Horizons - Subin Antony Jose; Jordan Jackson; Jayden Foster; Terrence Silva; Ethan Markham; Pradeep L. Menezes (Journal of Manufacturing and Materials Processing)
In-space manufacturing represents a transformative frontier in space exploration and industrial production, offering the potential to revolutionize how goods are produced and resources are utilized beyond Earth. This paper explores the multifaceted aspects of in-space manufacturing, including its evolution, technologies, challenges, and future prospects, while also addressing ethical and legal dimensions critical to its development. Beginning with an overview of its significance and historical context, this paper underscores key concepts such as resource optimization and the reduction of launch costs. It examines terrestrial and space-based manufacturing processes, emphasizing additive manufacturing, advanced materials processing, autonomous robotic systems, and biomanufacturing for pharmaceuticals. Unique challenges posed by the space environment, such as microgravity, vacuum conditions, and radiation exposure, are analyzed alongside issues related to supply chains, quality assurance, and energy management. Drawing from case studies, including missions aboard the International Space Station, this paper evaluates the lessons learned over six decades of innovation in in-space manufacturing. It further explores the potential for large-scale production to support deep-space missions and assesses the commercial and economic feasibility of these technologies. This paper also delves into the policy, legal, and ethical considerations to address as space-based manufacturing becomes integral to future space exploration and the global space economy. Ultimately, this work provides a comprehensive roadmap for advancing in-space manufacturing technologies and integrating them into humanity’s pursuit of sustainable and scalable space exploration.